1975
DOI: 10.1111/j.1600-0765.1975.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of gingival connective tissue in determining epithelial differentiation

Abstract: Free grafts of connective tissue, without epithelium, were transplanted from either the keratinized gingiva or the non-keratinized alveolar mucosa (controls) into areas of the alveolar mucosa in seven monkeys. The grafts were placed in pouches created in the connective tissue as close as possible to the overlying epithelium. After 3-4 weeks, the transplants were exposed by removal of the overlying tissue in order to allow epithelialization from the surrounding non-keratinized alveolar mucosa. The transplants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
174
1
12

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(197 citation statements)
references
References 35 publications
10
174
1
12
Order By: Relevance
“…been demonstrated that keratinization of the gingival epithelium is controlled by the morphogenetic stimuli of underlying connective tissue. 11,12 Therefore, the cultivated keratinocytes were not needed to guarantee subsequent keratinization. Based on these clinical cases, the tissue engineering technique offers several advantages if applied in cases of gingival augmentation: 1) a very small donor site (2 × 1 × 1 mm); 2) adequate amount of keratinized tissue obtained; 3) fine esthetic results; and 4) minimal discomfort for the patient.…”
Section: Case Seriesmentioning
confidence: 99%
“…been demonstrated that keratinization of the gingival epithelium is controlled by the morphogenetic stimuli of underlying connective tissue. 11,12 Therefore, the cultivated keratinocytes were not needed to guarantee subsequent keratinization. Based on these clinical cases, the tissue engineering technique offers several advantages if applied in cases of gingival augmentation: 1) a very small donor site (2 × 1 × 1 mm); 2) adequate amount of keratinized tissue obtained; 3) fine esthetic results; and 4) minimal discomfort for the patient.…”
Section: Case Seriesmentioning
confidence: 99%
“…Transplantation experiments have suggested that the typical papillary architecture and the features of the epithelium covering the connective tissue papilla result from the action of unknown connective tissue inducers (PLAGMANN et al, 1974;KARRING et al, 1975). It may be reasonably conceived that the differentiation in the anterior and posterior columns of the epithelium in the filif orm papilla may be controlled by the connective tissue papillae.…”
Section: Discussionmentioning
confidence: 99%
“…Melby and Karasek (1973) proposed two mechanisms to explain the influence of connective tissue on epithelial cells: 1) the connective tissue provides a physical substrate for attachment and orientation of epidermal basal cells; and 2) the connective tissue cells synthesize diffusible proteins that influence both growth and differentiation of epithelial cells. That diffusible factors of dermal origin facilitate growth and differentiation of the epithelial cells has long been considered relevant (Karring et al, 1975;Mackenzie and Fusenig, 1983;Mackenzie and Hill, 1984;Coulomb, 1989;Mackenzie et al, 1993). Mackenzie and Fusenig (1983) showed that even if keratinocytes have no direct contact with connective tissue, they still show full differentiation, thereby demonstrating that diffusible dermal products contribute to the differentiation of cultured keratinocytes.…”
Section: Discussionmentioning
confidence: 99%